PROJECT BASSED LEARNING: PRAKSIS DAN ANALISIS PENERAPAN PADA PEMBELAJARAN OTOMOTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMK - Suyitno; Mike Elly Anitasari; Indri; Purnomo, Bayu Gilang; Bahtiar, Fahmy Zuhda (Steam Engineering, 2024)
This research aims to: 1) Find out the application of the Project Based Learning (PJBL) based method in Basic Automotive Engineering (TDO) subjects with Measurement Subjects 2) To find out student learning outcomes after implementing the Project Based Learning (PJBL) based method in the subject Basic Automotive Engineering (TDO) with Measurement Subjects. This type of research is Class Action Research. This research was carried out in two cycles. The subjects of this action research were 30 class X TKR TKR students at Patriot Pituruh Purworejo Vocational School. After the data was obtained, it was analyzed using the percentage description technique. Based on the results in cycle II, it has been shown that student learning outcomes have increased, this can be seen from the increase in learning scores of students who scored more than 75 by 80%. Student learning outcomes in cycle II have achieved the desired indicators of success, namely students who get a score of 75 or more reach a percentage of 80%. The research results show that: Student learning outcomes and activeness increase with each cycle. This can be seen from the average value of the class in cycle I of 71.54, which increased in cycle II, namely 78.97. The percentage of student completion also increased, in cycle I the percentage of completion was 51.43%, increasing to 80% in cycle II.